2017
DOI: 10.1016/j.scitotenv.2016.09.193
|View full text |Cite
|
Sign up to set email alerts
|

Short- and medium-chain chlorinated paraffins in sediments from the middle reaches of the Yangtze River: Spatial distributions, source apportionment and risk assessment

Abstract: Chlorinated paraffins (CPs) are easily adsorbed into sediments where they pose potential risks to the ecosystem and human health. Few studies have investigated short- and medium-chain CPs (SCCPs and MCCPs) in sediments. The aim of the present study was to comprehensively investigate contamination levels, spatial distributions, sources and risks posed by CPs in sediments from the middle reaches of the Yangtze River. The sediment samples were analyzed by two-dimensional gas chromatography coupled with time-of-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The individual chlorination degrees of the CP groups were not provided, although the combined values of SCCPs and MCCPs in the car tire samples ranged from 60.5 to 62.5%. In general, the MCCP homologue pattern observed in our study was not unique, and comparable carbon and chlorine homologue MCCP patterns have been shown in various samples all over the world such as in sediment, , sewage sludge samples, house dust, , wildlife, , human blood, and in technical CP products used in Europe and China.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The individual chlorination degrees of the CP groups were not provided, although the combined values of SCCPs and MCCPs in the car tire samples ranged from 60.5 to 62.5%. In general, the MCCP homologue pattern observed in our study was not unique, and comparable carbon and chlorine homologue MCCP patterns have been shown in various samples all over the world such as in sediment, , sewage sludge samples, house dust, , wildlife, , human blood, and in technical CP products used in Europe and China.…”
Section: Resultssupporting
confidence: 83%
“…A relatively high variation of the CP concentrations in the car tires was observed compared to the recycled products (rubber granulates and playground tiles), probably because these products are composed of a mixture of multiple tires with high and low CP concentrations. CPs with carbon chain lengths lower than C 10 were recently found for the first time in sediment samples from China 24 and Sweden. 25 Only in one of the rubber samples, playground tile (PGT6), a C 9 CP was observed (SI Figure S2), which contributes 2% to the total SCCP concentration in this sample.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…The ∑SCCP concentrations in sediments were in the range of not detected (ND)-2020 ng g −1 . The obtained concentrations were lower than those obtained in other studies while similar to the ones obtained in some (Chen et al 2011;Gao et al 2012;Sun et al 2017;Xu et al 2019b;Zeng et al 2017b;Qiao et al 2016), whereas higher in comparison with two studies (Qiao et al 2017;Iozza et al 2008). However, the Mann-Whitney U test indicated that MCCP concentrations in sediments were higher than those of SCCPs (p <0.001), which was attributed to the use pattern of commercial CP formulations in China.…”
Section: Sedimentsupporting
confidence: 82%
“…In comparison with other studies, the results were similar to those obtained from previous studies (Pan et al 2011a;Pan et al 2011b), which confirmed that emissions from local factories were likely the main source of SCCPs in river sediment. Qiao et al (2017) also determined SCCP concentration in sediments from 13 locations in the middle reaches of the Yangtze River, which ranged from 4.19 to 41.6 ng g −1 dw and chlorine contents ranging from 61.8 to 63.8%. The obtained results were similar to those of Zeng et al (2012) and Zeng et al (2013a), but lower than those obtained by Gao et al (2012) and Ma et al (2014a).…”
Section: Sedimentmentioning
confidence: 99%
“…Among these three CP groups, SCCPs have generated great concern because of their high potential for biological toxicity, bioaccumulation, , and long-range transport. , In April 2017, SCCPs were listed as a new group of persistent organic pollutants (POPs) under the Stockholm Convention . As a result of this, increasing production and usage of SCCP alternatives such as MCCPs and LCCPs are expected. , Very short-chain CPs (vSCCPs, C 6–9 ) occur as byproducts or impurities in CP technical products , and have recently been found in manufactured products (lubricants and household hand blenders) and environmental matrices (e.g., sediments, biota, and human serum). vSCCPs are likely to have similar properties as SCCPs considering their short alkane chain length.…”
Section: Introductionmentioning
confidence: 99%